Atypical Presentation of Pretibial Myxoedema in Graves Disease - Islam, Quazi Tarikul; Momen, Abdul Basit Ibne; Khondokar, Abul Kashem; Ahasan, HAM Nazmul; Tahseen, Homayra (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Abstract not available J Bangladesh Coll Phys Surg 2017; 35(1): 46